2008
DOI: 10.1016/j.jpainsymman.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Pain Management: Caregiver Perceptions and Pain Talk by Hospice Interdisciplinary Teams

Abstract: As patients are cared for in their home by family caregivers, several challenges arise in effective pain and symptom management. Despite hospice's reputation as the gold standard for terminal care, there is still a need to improve pain management practices including challenges that caregivers face, related to pain assessment, reluctance and fear of administering medication, noncompliance with pain medicine regimens, and hesitance to report pain. The hospice philosophy of care promotes service for both patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 24 publications
3
47
2
1
Order By: Relevance
“…Furthermore, there is evidence that patients may wait until pain is significant before reporting it (Oliver et al, 2008) making the need for prompt response essential. A perceived lack of time is a significant contributory factor both to nurses' stress and to medication errors (Brady et al, 2009, Haigh andOrmandy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that patients may wait until pain is significant before reporting it (Oliver et al, 2008) making the need for prompt response essential. A perceived lack of time is a significant contributory factor both to nurses' stress and to medication errors (Brady et al, 2009, Haigh andOrmandy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Institutional Review Board of the sponsoring university approved this study. The survey was created based upon the findings of an earlier pilot study that explored the assessment of caregivers perceptions of managing their patient's pain (Parker Oliver et al, 2008). The survey asked questions related to the delivery of social work services in their hospice, the social workers' role within the team, their assessment and experience with caregivers related to pain management and their team meeting structure.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Recent research has reported that informal caregivers of hospice patients are not routinely assessed by social workers or any member of the hospice team, including their perceptions of pain medicines (Parker Oliver et al, 2008). The purpose of this study was to follow-up on those findings and assess if the issue was isolated to the hospices participating in the earlier study or if the lack of formal caregiver assessment by social workers is more widespread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides mandating specific supportive care professionals, the hospice Medicare guidelines require each of the aforementioned healthcare professionals to provide care in order for the hospice to be certified (CMS, 2012). The team members address the patient's "total pain" needs; a concept developed by Cicely Saunders as physical, psychological, social, and spiritual issues affecting a dying patient (Arber, 2007;Oliver et al, 2008;Saunders, 2001). …”
Section: The Hospice Modelmentioning
confidence: 99%